In vivo Comparison of the Duration between two Endodontic Instrumentation Techniques in Deciduous Teeth - Genara Brum Gomes (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2014)
Objective:To make an in vivo comparison of the amount of time required for root canal instrumentation of inferior deciduous molars either using rotary or manual techniques, and root canal filling of the same teeth. Material and Methods:Eight participants ranging from six to eight years of age that presented mandibular deciduous molars with root canal treatment indication were selected. Manual instrumentation with stainless steel K-files was performed in group I, and rotary instrumentation with Pro Taper rotary system was performed in group II.Results:T-test was used to determine mean value differences for the mesiolingual (ML) and distal (D) canals, showing no statistically significant differences (p=0.912 and p=0.366, respectively). The Mann-Whitney test was performed to detect mesiobuccal canal (MB) mean value differences, which were not statistically significant (p = 0.200). As to mean time required to perform canal filling for each group (manual and rotary) no statistically significant differences (p = 0.715) were found. Conclusion:Root canal preparation with rotary nickel-titanium instruments can be an alternative to mechanical instrumentation, although instrumentation and obturation time was not reduced.